Rediscovering parainfectious encephalopathy in the post-COVID-19 era - Bai, Lin; Geng, Chang; Guan, Hongzhi (Frontiers in Immunology, 2025)
The COVID-19 pandemic has unveiled the pivotal role of systemic inflammatory responses in neurological complications, particularly parainfectious encephalopathy. Accumulating evidence has established innate immune overreaction—distinct from direct viral neuro-invasion or autoantibody-mediated reaction—as the fundamental mechanism. The clinical manifestations of parainfectious encephalopathy are highly diverse, spanning from mild cases, such as mild encephalopathy with or without a reversible splenial lesion (MERS or ME), to catastrophic syndromes like acute necrotizing encephalopathy (ANE) and febrile infection-related epilepsy syndrome with or without a claustrum lesion (FIRES-C or FIRES). In this article, we summarize the phenotypes, diagnosis, and treatment strategies for parainfectious encephalopathy to enhance clinical recognition and understanding of this re-emerging disorder.